Measuring implementation climate: psychometric properties of the Implementation Climate Scale (ICS) in Norwegian mental health care services - Nadina Peters; Randi Hovden Borge; Ane- Marthe Solheim Skar; Karina M. Egeland (BMC, 2022)
Abstract Background Employees' perceptions of organizational climate for implementation of new methods are important in assessing and planning for implementation efforts. More specifically, feedback from employees' points to which implementation strategies to select, adopt, and tailor in building positive climate for implementation of new evidence-based practices within the organization. Implementation climate can be measured with the Implementation Climate Scale (ICS). The purpose of this study was to investigate the psychometric properties of the Norwegian version of the ICS in outpatient mental health clinics. Methods The ICS was administered to 383 clinicians within 47 different child and adult mental health clinics across the country. We conducted confirmatory factor analysis to assess the psychometric functioning of the ICS. Cronbach's alpha was examined to assess internal consistency. We also examined criterion related validity of the scale by comparing it with an alternative measure of implementation climate (concurrent validity) and by examining correlations with clinicians' intentions to use evidence-based practices. Results Results supported the 6-factor structure and the internal consistency reliability of the ICS. One exception was poor functioning of the Reward scale. Concurrent validity was stronger at the group than at the individual level, and assessment of associations with clinicians' intentions to use evidence- based practices showed positive correlations. Conclusions The Norwegian version of the ICS is a promising tool for assessing implementation climate which can provide organizations with specific feedback concerning which aspects of the implementation climate to attend to. Due to poor functioning of the Reward scale, adaptations and further testing of this is recommended.